A case of focal segmental glomerulosclerosis syndrome secondary to high-altitude polycythemia. (13th September 2013) - Yin, Qinghua; Yang, Yingying; He, Tao; Lai, Chunyou; Liang, Yaping; Jiang, Wei; Wang, Hui; Tang, Xi; Diao, Yongshu; Huang, Songmin; Fu, Ping; Liu, Fang
Abstract: In recent years, focal segmental glomerulosclerosis has become the commonest cause of the nephrotic syndrome seen in adults. Secondary focal segmental glomerulosclerosis is observed when glomerular workload is increased. We report a case of focal segmental glomerulosclerosis with nephrotic syndrome secondary to high-altitude polycythemia (HAPC). Our case points out that for patients with focal segmental glomerulosclerosis, who presented with nephrotic syndrome secondary to HAPC, treatments for HAPC are crucial for the reduction of proteinuria and renal protection instead of glucocorticoid and immunosuppressive drugs.